Transseptal Access for Catheter Ablation of Left-Sided Atrioventricular Accessory Pathways in Children - Meshkova, M.; Doronin, A.; Khanenova, V.; Rudenko, N. (Ukrainian Journal of Cardiovascular Surgery, 2021)
Introduction. Puncture of the atrial septum for access to the left atrium is often used for cardiac interventions in adults. In children, transseptal puncture is a less common, technically more difficult procedure, and the frequency of its complications is not well described in the literature. Objective. Our aim was to study the feasibility and safety of transseptal puncture in children through retrospective analysis of 208 consecutive radiofrequency catheter ablations (RFCA) for left-sided atrioventricular accessory pathways (AP). Results and discussion. Successful transseptal puncture was possible in 100% of cases, ablation in 97%. The mean time, including mapping and radiofrequency ablation, was 40 ± 22 minutes, and the mean fluoroscopy time was 3.8 ± 1.9 minutes. There were no complications associated with transseptal puncture. Recurrence of AP was reported in 6 (2.9%) children. Residual atrial septal defects 1 year after the procedure were detected by echocardiography in 5 (2.4%) children. The transseptal access ensures successful and effective ablation of the left-sided accessory pathways in the vast majority of children. RCA with transseptal access has a total operative time and fluoroscopy time comparable to those described in the literature for RCA with retrograde access. The reduced duration of the procedure and the fluoroscopy time are of great importance in the pediatric age group, which is most vulnerable to drug and radiation exposure. However, transseptal puncture in children remains a technically complex intervention with the possibility of corresponding complications. It should be performed by an experienced electrophysiologist who has experience in pediatric catheter ablation. Conclusions. Transseptal puncture is a feasible and reasonably safe procedure for children. It can be considered as the first choice approach in children with left-sided accessory pathways.